On the Erdős-Sós Conjecture for graphs on n = k + 4 vertices - Yuan, Long-Tu (Ars mathematica contemporanea, 2017)
The Erdős-Sós Conjecture states that if ?$G$? is a simple graph of order ?$n$? with average degree more than ?$k-2$?, then ?$G$? contains every tree of order ?$k$?. In this paper, we prove that Erdős-Sós Conjecture is true for ?$n=k+4$?.
Keywords: drevo; Erdős-Sósova domneva; maksimalna stopnja; teorija grafov